Application Value Assessment of Grid Side Energy Storage Under Typical Scenarios in China - Bibin HUANG; Jing HU; Liping JIANG; Qionghui LI; Kaihui FENG; Bo YUAN (Zhongguo dianli)
China attaches great importance to the energy storage development. Grid side energy storage is an important way to achieve large-scale energy storage development. Combined with the technical and economic characteristics of energy storage and the demand of power system, this paper introduces several general understandings of the gird side energy storage application in China. The grid side energy storage should be integrated into power planning with comprehensive consideration of the security, economic and social benefits, and it is necessary to optimize the total scale, layout and technical types of grid side energy storage. Based on the typical scenarios such as ensuring power system security, ensuring the function of power transmission and distribution, reducing the loss of power grid and improving the utilization level of new energy, a research is carried out on the grid side energy storage application value. The research results show that pumped storage, as a system-level regulation measure, should be planned with a certain scale. Electrochemical energy storage, whose cost is still relatively high, still needs to improve the economy through reasonable planning, and its future large-scale development relies on the market.